2004
DOI: 10.1098/rsbl.2004.0216
|View full text |Cite
|
Sign up to set email alerts
|

Face processing in humans is compatible with a simple shape–based model of vision

Abstract: Understanding how the human visual system recognizes objects is one of the key challenges in neuroscience. Inspired by a large body of physiological evidence, a general class of recognition models has emerged, which is based on a hierarchical organization of visual processing, with succeeding stages being sensitive to image features of increasing complexity. However, these models appear to be incompatible with some well-known psychophysical results. Prominent among these are experiments investigating recogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
102
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(119 citation statements)
references
References 20 publications
16
102
1
Order By: Relevance
“…Several studies suggested that face inversion disturbs the processing of configural/holistic information in a face more than that of the facial features either overall across the entire face (Rhodes et al, 1993;Cabeza and Kato, 2000;Freire et al, 2000;Leder and Bruce, 2000;Barton et al, 2001;Leder et al, 2001;Rossion and Gauthier, 2002;Leder and Carbon, 2006) or at least in the lower, mouth region (Xu and Tanaka, 2013;Tanaka et al, 2009). Other studies, however, emphasize that the processing of featural and configural information are equally disrupted by face inversion (Riesenhuber et al, 2004;Yovel and Kanwisher, 2004; for a review see Tanaka and Gordon, 2011). Despite the lack of consensus regarding the details 2 , common to all these studies is the assumption that certain mechanisms, exclusively involved in the processing of upright faces are interrupted by picture-plane inversion.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggested that face inversion disturbs the processing of configural/holistic information in a face more than that of the facial features either overall across the entire face (Rhodes et al, 1993;Cabeza and Kato, 2000;Freire et al, 2000;Leder and Bruce, 2000;Barton et al, 2001;Leder et al, 2001;Rossion and Gauthier, 2002;Leder and Carbon, 2006) or at least in the lower, mouth region (Xu and Tanaka, 2013;Tanaka et al, 2009). Other studies, however, emphasize that the processing of featural and configural information are equally disrupted by face inversion (Riesenhuber et al, 2004;Yovel and Kanwisher, 2004; for a review see Tanaka and Gordon, 2011). Despite the lack of consensus regarding the details 2 , common to all these studies is the assumption that certain mechanisms, exclusively involved in the processing of upright faces are interrupted by picture-plane inversion.…”
Section: Discussionmentioning
confidence: 99%
“…This has been illustrated by the fresh perspective that computational modelling has afforded of the distinction between part-based and configural processing of objects and faces 117 . Computational evidence has also revealed that image fragments of intermediate complexity are more informative for object categorization than fragments of low or high complexity 118,119 , suggesting that neural coding in object-selective areas might be based on such intermediate-complexity shape features.…”
Section: Object Category As a Basic Propertymentioning
confidence: 99%
“…Most importantly, researchers have found that inversion in the picture plane impairs how observers performed with facial configurations rather than facial features (Collishaw & Hole, 2002;Freire, Lee, & Symons, 2000;Goffaux & Rossion, in press;Leder, Candrian, Huber, & Bruce, 2000;Tanaka & Farah, 1993). Others have found that inversion simply affects how efficiently facial features are processed (Sekuler, Gasper, Gold, & Bennett, 2004;Riesenhuber, Jarudi, Gilad, & Sinha, 2004;Yovel & Kanwisher, 2004). By comparison, nonface objects may be recognized primarily on the basis of features and coarse spatial relations (Biederman, 1987) without a corresponding reliance on metric configurations of features.…”
Section: Introductionmentioning
confidence: 99%